On the identity of Clausena smyrelliana, and two new combinations in C. anisum-olens (Aurantioideae, Rutaceae) - Molino, Jean-François (Phytotaxa, 2017)
Clausena smyrelliana Forster (2000: 716) was described from several gatherings collected from a few plants growing in littoral microphyll vineforests of South-East Queensland, Australia. Because of its rarity and of severe threats on its natural habitat, it has been listed as ‘Endangered’ under Queensland’s Nature Conservation Act 1992 (Atlas of Living Australia 2015). However, the combination of a long style (> 1/2 pistil length), lack of gynophore, straight staminal filaments, subcylindrical buds, and corymbiform inflorescence, excludes this species from Clausena Burman (1768: 87) and places it into Murraya J.Koenig (in Linné 1771: 554) (Molino 1994: 107)